Blood flow dynamics during local photoreaction in a head and neck tumor model - Rohrbach, Daniel J.; Tracy, Erin C.; Walker, Jessica; Baumann, Heinz; Sunar, Ulas (Frontiers in Physics, 2015)
We have applied continuous blood flow dynamics, quantified with diffuse correlation spectroscopy (DCS), in investigating photodynamic therapy (PDT) induced local photoreaction in a head and neck tumor model. Photoclor (0.47 µmol/kg) was intravenously administered 24 hour before PDT. Two types of fluence rates were implemented: Low fluence rate (14 mW/cm2) and high fluence rate (75 mW/cm2). The total delivered fluence was 100 J for both types. We observed that PDT induced substantial vascular shut down in both types. While the shutdown was persistent in tumors exposed to low fluence rate PDT, the shutdown was transient in tumors exposed to high fluence PDT. Loss of microvascular structures was confirmed by the microscopic analyses of tumor section following immunostaining for CD31. Blood flow dynamics related metrics were also strongly correlated with crosslinking of STAT3, a molecular marker of photoreaction. STAT3 analysis indicated that low fluence rate yields a substantially higher photoreaction, and, thus, a more effective PDT. Our results indicate that noninvasive blood flow measurements can monitor the efficacy of PDT in real-time and potentially provide a feedback for its optimization.